Usages différenciés de documents pédagogiques en sciences : étude de quelques raisons - Éliane Pautal (Recherches en Éducation)
This article deals with the use of a document, drafted by the teacher, in teaching and learning about the concept of blood circulation at primary school. We believe that the use of this document in the classroom might explain, partly, the production of inequality during science learning and we focus on understanding some of the reasons that could motivate these differentiated uses. The case study offers didactic interpretation by mobilizing an analytical framework of the practices developed by Sensevy et al. (Sensevy, Mercier & Schubauer-Leoni, 2000; Sensevy & Mercier, 2007; Sensevy, 2011), along with the concept of relationship to knowledge (Charlot, Bautier & Rochex, 1992; Charlot, 1997; Bautier & Rochex, 1998; Bautier & Goigoux, 2004; Bautier & Rayou, 2009). This double theoretical framework allows us to shed light on the production of inequality in science class, referring in part to the teacher and/or to the pupils and the institution.